2020
DOI: 10.1155/2020/4986365
|View full text |Cite
|
Sign up to set email alerts
|

BRCA Mutations in Prostate Cancer: Prognostic and Predictive Implications

Abstract: Despite chemotherapy and novel androgen-receptor signalling inhibitors (ARSi) have been approved during the last decades, metastatic castration-resistant prostate cancer (mCRPC) remains a lethal disease with poor clinical outcomes. Several studies found that germline or acquired DNA damage repair (DDR) defects affect a high percentage of mCRPC patients. Among DDR defects, BRCA mutations show relevant clinical implications. BRCA mutations are associated with adverse clinical features in primary tumors and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 44 publications
4
88
0
1
Order By: Relevance
“…BRCA2 was reported to have the highest relative risk of metastases when compared with men who do not have PCa [ 31 ]. DNA damage repair defects (DDR) represent 25% of these alterations, with BRCA2 mutations being the most frequently observed [ 6 ]. A second analysis by Dall’Era et al looked at both somatic and germline DNA alterations in men with both localized and metastatic disease.…”
Section: Advancement In Diagnostic Strategies Aiding Selection Of mentioning
confidence: 99%
See 2 more Smart Citations
“…BRCA2 was reported to have the highest relative risk of metastases when compared with men who do not have PCa [ 31 ]. DNA damage repair defects (DDR) represent 25% of these alterations, with BRCA2 mutations being the most frequently observed [ 6 ]. A second analysis by Dall’Era et al looked at both somatic and germline DNA alterations in men with both localized and metastatic disease.…”
Section: Advancement In Diagnostic Strategies Aiding Selection Of mentioning
confidence: 99%
“…It can also have family implications if a germline mutation is identified. Germline BRCA2 mutations are associated with higher risk of PCa development, risk of local treatment failures and mortality [ 6 ]. More importantly, these alterations are clinically actionable and can be therapeutically targeted with Poly (adenosine diphosphate ribose) polymerase (PARP) inhibition or by immune checkpoint inhibition.…”
Section: Advancement In Diagnostic Strategies Aiding Selection Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a growing body of evidences suggest that germline and somatic mutations on DNA repair genes should be investigated in patients with prostate cancer due to the development of PolyAdenosine Diphosphate (ADP)-Ribose Polymerase (PARP) inhibitors (16). It has been estimated that alterations in DNA Damage Repair (DDR) genes can be found in approximately 11% of prostate cancers (17).…”
Section: Tumor Genetic Landscapementioning
confidence: 99%
“…Towards identification of patient specific optimal sequences for these future therapeutic measures, there is a growing requirement for identification of suitable biomarkers to guide effective treatment selection and characterization of treatment responses [24]. Recently, a number of genomic aberrations have been proposed as predictive biomarker for evaluation of treatment response profiles like cyclin-dependent kinase 12 (CDK12) and DNA damage repairs (DDR) associated breast cancer gene 1 (BRCA1) as well as ataxia telangiectasia mutated (ATM) in CRPC patients [142,143]. It has been suggested that the biallelic loss of CDK12 are prevalent in around 5% of metastatic CRPCs and intrinsically associated with immunosuppression through massive infiltration of CD4 + FOXP3 − T lymphocytes in prostate TME, which strongly urges for the interventions with immunotherapeutic approaches [142].…”
Section: Future Challenges In Individualized Combination Therapymentioning
confidence: 99%